HUBUNGAN ANTARA FAKTOR KUALITAS PRODUK, KUALITAS PELAYANAN, LOKASI DAN LINGKUNGAN DENGAN KEPUTUSAN PEMBELIAN SUSU SEGAR - Robertus Eri Triawan; Hendrik Johannes Nadapdap; Bayu Nuswantara (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2019)
The fresh milk is an animal food that has high nutrition and provides great benefits for humans. At present the development of fresh milk sales in Salatiga is experiencing rapid development in line with the growing culinary place. The decision to buy fresh milk is an interaction of internal and external factors within the scope of marketing. The purpose of this study was to determine the relationship between product quality, service quality, location and environment with the decision to remove fresh milk at the Salatiga Stasiun Susu cafe. This type of research is quantitative descriptive using the survey method. Data collection is done by observation and interviews using questionnaires. The research location was set deliberately at the Salatiga Stasiun Susu cafe. Sampling uses a non-probability sampling of visitors 16 to 25 years old who consume and buy fresh milk at the Susu Stasiun cafe. The sampling technique was done by accidental sampling with a total of 50 respondents. Data analysis with rank spearman. The results showed that there was a positive and significant relationship between product quality, service quality, location and environment to the decision to purchase fresh milk.